The Impact of Fintech, Sustainability Banking, and Natural Resources on Environmental Sustainability - Maulana, Yasir; Nugraha, Nugraha; Disman, Disman; Sari, Maya; Jahidah, Nurul Siti (Jurnal Riset Ilmu Ekonomi, 2025)
This study aims to analyze the role of FinTech, sustainable banking, and natural resource revenues collectively influencing environmental outcomes in the ASEAN Plus Three region is still scarce. This study uses panel data regression analysis covering nine ASEAN Plus Three countries over the period 2017 to 2021. The findings provide evidence of the significant influence of FinTech, Sustainable Banking, and natural resource revenues derived from sustainable environmental development activities in Plus Three economies. FinTech has a very negative effect on environmental outcomes. In contrast, sustainable banking does not show a statistically significant effect. Natural resource revenues are positively related to environmental degradation. These results highlight the importance of implementing low-carbon technologies to meet carbon neutrality targets in ASEAN Plus Three countries. The findings offer empirical insights for policymakers to prioritize green technologies, reassess fintech's environmental footprint, and strengthen the sustainable banking framework.